Iccrem 2015 2015
DOI: 10.1061/9780784479377.095
|View full text |Cite
|
Sign up to set email alerts
|

Acceptance and Use of LCC as a Decision Support Tool for Renovation Investments

Abstract: This paper seek to explain why LCC is used or not for renovation projects. The study is based on a theoretical explanation model called the Technology Acceptance Model (TAM). The model assumes that a number of factors determine whether and when individuals will use a particular technology. Two main components of the model are (1) Perceived usefulness, and (2) Perceived ease of use. The response rate was 32,3%. The results show that the climate in terms of the extent to which LCC is advocated and used by collea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 9 publications
1
3
0
Order By: Relevance
“…The question arises whether or not the adoption of LCC really is as slow as claimed, or if there is a discrepancy between the way researchers idealistically picture how LCC should be used and practitioners' ways of using LCC in practice. In a recent study about construction clients it was in fact found that the vast majority used LCC within their organization (Gluch & Gustafsson, 2015), which agrees with the interview observations made by Olsson et al (2015). However, Olsson et al (2015) found a large variation in the way LCC was used.…”
Section: Introductionsupporting
confidence: 74%
See 1 more Smart Citation
“…The question arises whether or not the adoption of LCC really is as slow as claimed, or if there is a discrepancy between the way researchers idealistically picture how LCC should be used and practitioners' ways of using LCC in practice. In a recent study about construction clients it was in fact found that the vast majority used LCC within their organization (Gluch & Gustafsson, 2015), which agrees with the interview observations made by Olsson et al (2015). However, Olsson et al (2015) found a large variation in the way LCC was used.…”
Section: Introductionsupporting
confidence: 74%
“…TAM explains the adoption of various types of technical systems and applications (Davis, 1989) and has been used to explain tool uptake in various types of contexts, such as office tools, software tools and business application tools, as well as various technological systems and applications (see review in Legris, Ingham, & Collerette, 2003). TAM has in a previous study been found useful for describing and understanding factors influencing LCC use (Gluch & Gustafsson, 2015). In brief, TAM explores external influence, perceived usability, attitudes towards use and intention to use.…”
Section: Questionnaire Survey Designmentioning
confidence: 99%
“…LCC can therefore, significantly define the success of a project as it incorporates all the costs associated with the project through life. Literature further evidences the diverse applications of LCC including its ability to perform as a decision support tool (Meng and Harshaw, 2013;Gluch and Gustafsson, 2015;Minhas and Potdar, 2020), enhance sustainability (Caplehorn, 2012;Alaloul et al, 2021), and ensure value for money (Swaffield and McDonald, 2008). However, majority of research on LCC concerns tool modelling and development, and surprisingly few studies pay interest into how practitioners perceive the usefulness of the tools developed (Goh and Sun, 2016).…”
Section: Life Cycle Costing In Constructionmentioning
confidence: 99%
“…OPERA-MILP is based on mixed integer linear programming (MILP) and was first developed at the Division of Energy Systems in Linköping University during the 1980s. The software has been used for studying both multi-family buildings (Gluch & Gustafsson, 2015;Gustafsson, 1990Gustafsson, , 2000Gustafsson, , 2001, and also one heritage single-family building (Broström et al, 2014).…”
Section: Life Cycle Cost Optimization -Opera-milpmentioning
confidence: 99%